2023
DOI: 10.1038/s41467-023-36855-9
|View full text |Cite
|
Sign up to set email alerts
|

Antigen discrimination by T cells relies on size-constrained microvillar contact

Abstract: T cells use finger-like protrusions called ‘microvilli’ to interrogate their targets, but why they do so is unknown. To form contacts, T cells must overcome the highly charged, barrier-like layer of large molecules forming a target cell’s glycocalyx. Here, T cells are observed to use microvilli to breach a model glycocalyx barrier, forming numerous small (<0.5 μm diameter) contacts each of which is stabilized by the small adhesive protein CD2 expressed by the T cell, and excludes large proteins including CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…It is therefore possible that the membrane receptors at the actin foci site experience transitions in micro- and nano-scale forces during different phases of the foci lifetime, enabling mechanotransduction. Indeed, recent studies have indicated the role of adhesion receptors such as CD2 in physically supporting TCR signaling 55 , and WASP functionally interacts with CD2 protein, indicating that there may be a connection between WASP and adhesion at the immunological synapse 56 . Our study in its current form does not discriminate between these possibilities and future experiments will be required to dissect them.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that the membrane receptors at the actin foci site experience transitions in micro- and nano-scale forces during different phases of the foci lifetime, enabling mechanotransduction. Indeed, recent studies have indicated the role of adhesion receptors such as CD2 in physically supporting TCR signaling 55 , and WASP functionally interacts with CD2 protein, indicating that there may be a connection between WASP and adhesion at the immunological synapse 56 . Our study in its current form does not discriminate between these possibilities and future experiments will be required to dissect them.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation, which is a consequence of the system used, is lack of imaging data of the interface between THP-1 cells and CHO cells. Advanced microscopy, beyond the scope of this study, is likely needed to image the molecular events in the microvilli-like structures and close contact areas involved in NTR triggering at cell-cell interfaces (Jenkins et al, 2023; Jung et al, 2021; Stinchcombe et al, 2023). A third limitation is that we only test one prediction of the KS model, that elongation of the receptor/ligand complex will abrogate NTR triggering.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was subsequently termed the kinetic segregation (KS) model (van der Merwe et al, 2000). Subsequent studies from multiple laboratories using a wide range of techniques have demonstrated that the KS mechanism plays a key role in TCR triggering (Burroughs et al, 2006; Chang et al, 2016; Chen et al, 2021; Choudhuri et al, 2005; Cordoba et al, 2013; James and Vale, 2012; Jenkins et al, 2023; Razvag et al, 2018; Schmid et al, 2016; Varma et al, 2006; Wilhelm et al, 2021). Recently it has been shown that synthetic receptors based on the TCR, namely chimeric antigen receptors (CARs), also appear to trigger by the KS mechanism, which has important implications for the design of these receptors and selection of their target antigens (Xiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…‘Microscope 1’ is a bespoke widefield fluorescence microscope, with the illumination entering the microscope body through the back illumination port, and has been described before. (43) For completeness, the excitation path combined a 488 nm laser (iBeam-SMART, Toptica), and the 561 nm laser (LaserBoxx, DPSS, Oxxius). Each laser beam was circularly polarized using quarter-wave plates, collimated, and expanded to minimize field variation.…”
Section: Methodsmentioning
confidence: 99%